Die hethitischen Vasallenverträge und die biblische Bundeskonzeption - Christiansen, Birgit (Biblische Notizen, 2013)
The comparison between the ancient near eastern treaty tradition and the biblical covenant conception always played a central role in the studies dedicated to the history of the religious relations between the ancient near eastern and the biblical world. It is maintained here that the Hittite treaties and other documents which share structural and functional similarities with them did not directly influence the biblical covenantal theology; nonetheless they are very important for the investigation of the ancient near eastern treaty tradition and the understanding of the biblical covenant conception. This contribution offers on the one hand an overview on the corpus of the Hittite treaties, their peculiar features and the history of the studies dedicated to them, while on the other hand it investigates the theological importance of the oath taking as part of the ratifying of a treaty. The resulting improved understanding of the Hittite treaty conception allows new insights also into the Old Testament covenantal theology.